THE ISSUE ON DETERMINATION OF TYPOLOGICAL FEATURES OF PEOPLE, COMMITTING CRIMINAL OFFENSES RELATED TO THE FORGERY OF EXCISABLE GOODS, AS AN ELEMENT OF THE CRIMINALISTIC CHARACTERISTICS - Zauresh, Ayupova; Yernar, Begaliyev; Zholdybay, Uspanov (International Journal of Research -GRANTHAALAYAH, 2019)
In the article «The issue on determination of typological features of people, committing criminal offenses related to the forgery of excisable goods, as an element of the criminalistic characteristics» prepared by doctoral student Ayupova Z.N.; Professor of the Department of Special Legal Disciplines, Doctor of juridical Science Begaliev E.N; Dean of the Faculty of Social Sciences and Law, candidate of juridical Sciences, Professor UspanovZh.T. The main purpose of this article is to identify the most characteristic features of an intruder's personality and to formulate recommendations aimed at improving the process of investigating criminal offenses related to falsification of excise goods. The article deals with the issue of theoretical interpretation of the concept of "criminalistic characterization of crimes" and "typology of personality" as its element. The analysis of the reference paper is given regarding the study of the typology of persons committing criminal offenses; as well as the problems that arise in determining the subject of the crime and the ways to solve them. The types of persons committing criminal offenses connected with forgery of excisable products as exogenous and endogenous types of intruders are investigated; classified by the object of encroachment, the nature of criminal acts, the degree of public danger. The concepts of socially-adoptive, socially-disadaptive type of personality of persons who commit this category of a criminal offense are disclosed. The structure of the personality of the intruder who deals in the falsification of excisable goods has been compiled and examined through socio-demographic, criminally-legal, socially significant physiological features and moral properties. The analysis of methods for establishing a suspect person is given, the main types of malefactors and their functions are identified in the production of a surrogate excise product. Recommendations for persons conducting investigations into criminal cases related to forgery of excise goods are developed.